The use of canva–based learning media to improve the ability to write procedure text for students - Risnawaty, Risnawaty; Fadhilah, Ihsan; Sutikno; Ningsih, Ayu Melati; Kristiana, Vera; Siregar, Muhammad Hatta (Jurnal Konseling dan Pendidikan, 2025)
This classroom action research (CAR) examines the efficacy of Canva-based learning media in enhancing secondary students’ procedural writing skills. Addressing the common challenges of structuring logical sequences and articulating details in procedural texts, the study involved 30 tenth-grade students at an Indonesian public high school, selected through purposive sampling due to persistent difficulties in writing tasks. Over two iterative cycles, Canva’s visual design tools—templates, icons, and multimedia elements—were integrated into instructional strategies to scaffold students’ understanding of procedural text components (goal, materials, steps). Data were triangulated through pre- and post-tests, observational checklists, and student questionnaires, analyzed quantitatively via descriptive statistics and qualitatively through thematic coding. Results demonstrated significant progress: mean scores rose from 62.3 (pre-test) to 82.4 (Cycle 2), with pass rates (≥65) surging from 30% to 90%. Observational data revealed increased engagement, with active participation climbing from 65% (Cycle 1) to 90% (Cycle 2), while questionnaires indicated 90% of students credited Canva for improved idea organization. The intervention’s success aligns with Mayer’s Cognitive Theory of Multimedia Learning, as dual-coding visual-textual stimuli reduced cognitive load and reinforced retention. Additionally, collaborative features in Canva fostered peer feedback, aligning with Vygotsky’s social constructivism. Challenges in Cycle 1, such as incoherent transitions, were remediated in Cycle 2 through focused editing exercises and animated simulations. The study underscores Canva’s potential as a pedagogical tool for procedural writing, emphasizing its accessibility and capacity to bridge creativity with structured learning. Recommendations include teacher training in digital design tools and further research on Canva’s applicability across diverse text genres and educational contexts.